Strengthening the Bachelor of Library and Information Science curriculum in the Philippines - Irinco, Reina R. (2001)
This study, in view of the changing information environment in the Philippines, attempted to determine the effect of Republic Act 6966 (law that allows Bachelor of Science in Education (BSE), Bachelor of Elementary Education (BEED), and Bachelor of Secondary Education (BSEd) majoring in library science to take the licensure examination for librarians) and the possible ways of revitalizing the library and information science programs that are currently offered in the nine colleges and universities in Metro Manila.